Immunostimulant Activity of Marchantia paleacea Bertol. Herb Liverwort Ethanol Extract in BALB/c Mice - Purkon, Dicki Bakhtiar; Iwo, Maria Immaculata; Soemardji, Andreanus A.; Rahmawati, Siti Farah; Fadhlillah, Faizah Min; Nadhifah, Ainun (Indonesian Journal of Pharmacy, 2021)
Immunostimulants are compounds that can stimulate an immune response by increasing the activity of non-specific and specific components of the immune system (humoral and cellular) against certain infections and diseases. The liverwort plant species Marchantia paleacea Bertol. has long been used as a source of nutrition and empirical medicine. However, scientifically there is still not much research data on immunomodulators in these plants. This study aims to determine the activity of immunomodulators in the ethanol extract of the herb Marchantia paleacea Bertol. in male mice of BALB/c strain. Bioactive compounds from this plant were extracted by maceration method using 96% ethanol. Extract characterization and phytochemical screening were determined according to WHO guidelines and standard procedures from previous studies. The immunomodulatory activity of the extract was tested by carbon clearance method and lymphoid organ index (non-specific responses), primary and secondary antibody titer tests (humoral specific responses), IL-2 cytokine levels and IFN-ɣ from serum secondary antibodies and delayed-type hypersensitivity reaction/DTH (cellular specific response). The results of qualitative phytochemical screening contained flavonoid compounds, saponins, phenolics, tannins and steroids/triterpenoids. The results of the non-specific immune response immunomodulator test showed that the dose of 52 mg/kg bw had the largest phagocytic index of 1.52 which included strong immunostimulation (K > 1.5) and the organ spleen index of 0.55 ± 0.11 which increased significantly compared to the control (p<0.05). The data on the acquisition of specific immune responses in the primary and secondary antibody titer test in the three test extracts resulted in increased titer levels compared to the control and at a dose of 52 mg/kg bw could significantly increase the levels of IL-2 cytokines in the control group (p<0,05). Meanwhile, in the DTH test, doses of 13 and 26 mg/kg bw could significantly increase the thickness of the soles of mice compared to controls (p<0.05).